Accuracy of Nutritional Status Assessment Tools for the Diagnosis of Malnutrition in Hospitalized Elderly Cancer Patients. (14th June 2022) - Stefani, Giovanna; Crestani, Mariana; Scott, Laura; Steemburgo, Thais
Abstract: Objectives: To evaluate in elderly hospitalized patients with cancer the accuracy of the Subjective Global Assessment - Patient-Generated (PG-SGA), PG-SGA short form (SF), Mini Nutritional Assessment (MNA) SF and Global Leadership Initiative on Malnutrition (GLIM) criteria using the handgrip Strength (HGS) and calf circumference (CC) for the diagnosis of malnutrition considering Subjective Global Assessment (SGA) as a reference and, to establish the association of malnutrition with length hospital stays (LOS). Methods: This is a cross-sectional study involving elderly inpatients with cancer. Nutritional status was identified within the first 48 hours of admission by SGA, PG-SGA, PG-SGA SF, MNA SF and GLIM (using HGS and CC). Area Under Curve (AUC) by receiver operating characteristic (ROC) curve, Sensitivity (Se), Specificity (Sp) and kappa (k) were analyzed. Association between malnutrition and LOS was investigated by logistic regression analysis, adjusted for confounding variables. Results: 155 patients were evaluated [69.8 ± 7.4 years, 60% male and 47, 7% of elderly patients were hospitalized for ≥ 5 days]. Malnutrition was diagnosed in 54.2%, 83%, 66%, 70%, 50% and 72% according to SGA, PG-SGA, PG-SGA SF, MNA SF, GLIM (using CC) and GLIM (using HGS), respectively. When we evaluated the accuracy, two tools showed better performance and moderate agreement compared to reference method (SGA): GLIM using CC (AUC: 0.789; Se: 76.2%; Sp: 81.7% and k = 0.574) and PG-SGA SF (AUC: 0.782; Se: 91.7%; Sp: 64.8% and k = 0.576). In logistic regression, the presence of malnutrition by SGA, PG-SGA SF, MNA SF and GLIM criteria, using CC, was significantly associated with LOS ≥ 5 days, but not by PG-SGA and GLIM using HGS. Conclusions: The PG-SGA SF and GLIM, using CC, are useful tools for diagnosing malnutrition and were associated with LOS ≥ 5 days in hospitalized elderly cancer patients. Funding Sources: Fundo de Incentivo à Pesquisa (FIPE) do Hospital de Clínicas de Porto Alegre, Rio Grande do Sul, Brazil. (number# 2019/0708).